Rekonstruksi Makna Pluralitas sebagai Media Integrasi Sosial dalam Melawan Konflik di Indonesia - Khasanah, Lutfi Uswatun; Maulana, Muhammad Dhewa; Ma’ruf, Roisul (Lembaga Yasin AlSys, 2022)
Religious people today face the greatest theological challenge of defining themselves in the midst of religious pluralism. In the Indonesian context, sometimes the greatest theological task actually arises among religious people. In this connection, it was also pointed out that the encounters between different religious leaders became more intense in order to discuss people's problems. At the individual level, their relationships seem to be in harmony. However, at the theological level, there are still significant obstacles, both at the religious elite level and at the general public. At this level, religious truth is conditioned as absolute and we do not know more than one. For this reason, religious pluralism as a medium of social integration in the context of strengthening national unity and integrity is urgently needed.